The Correlation Between Clean and Healthy Living Behavior Towards Covid-19 Prevention in School-Age Children in Pahonjean 06 State Elementary School, Majenang - Tasy Gustiyana; Atika Dhiah Anggraeni; Vivi Leona Amelia (UM Purwokerto Press, 2022)
Background: Clean and healthy living behavior is a behavior to improve health in order to realize a quality life. Covid 19 is a dangerous disease caused by the Sars-Cov2 virus. One way that can be done to prevent Covid-19 is by implementing clean and healthy living behaviors in everyday life. Objective: This study aims to determine the correlation between clean and healthy living behavior and prevention of COVID-19 in school-age children. Method: The research design is descriptive quantitative correlation with cross sectional approach. The sample in this study was 61 respondents using purposive sampling method and chi square analysis. Results: The results showed a correlation between clean and healthy living behavior on the prevention of covid-19 in school-age children, with a value of -value = 0.009. Most of the respondents were women with 40 respondents (65.6%) with the age of the respondents being 11 years old. Conclusion: There is a correlation between clean and healthy living behavior and prevention of covid-19 in school-age children at SD Negeri Pahonjean 06 Majenang.